1995
DOI: 10.1038/hdy.1995.109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of quantity and quality of environmental stress on multilocus heterozygosity-growth relationships in Eisenia fetida (Annelida: Oligochaeta)

Abstract: The effects of environmental quantity (moderate soil moisture vs. low soil moisture) and quality (low soil moisture vs. low temperature) on multilocus heterozygosity (MLH)-growth relationships were tested in the earthworm Eisenia fetida. The control treatment was high soil moisture and high temperature. Fresh weight was measured weekly for 4 weeks; MLH was computed for eight polymorphic loci. Moderate moisture limited growth (change in fresh weight) to 50 per cent of control growth; both low moisture and low t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
3

Year Published

1996
1996
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 27 publications
1
18
3
Order By: Relevance
“…Significant MLH-fresh weight relationships were only detected at the beginning of the life history (a negative correlation), and toward the end of the life history (positive correlations) for individuals pooled among environments. These patterns also differ from those studies that showed significant MLH-growth correlations early in ontogeny (about weeks 2-4) for this species (Audo and Diehl, 1995). The current patterns are compatible however with the selection reversal hypothesis of Gaffney et al (1990) to explain the frequent association of a heterozygote deficiency and heterosis in natural populations of marine bivalves.…”
Section: Tc Mcelroy and Wj Diehlcontrasting
confidence: 54%
See 2 more Smart Citations
“…Significant MLH-fresh weight relationships were only detected at the beginning of the life history (a negative correlation), and toward the end of the life history (positive correlations) for individuals pooled among environments. These patterns also differ from those studies that showed significant MLH-growth correlations early in ontogeny (about weeks 2-4) for this species (Audo and Diehl, 1995). The current patterns are compatible however with the selection reversal hypothesis of Gaffney et al (1990) to explain the frequent association of a heterozygote deficiency and heterosis in natural populations of marine bivalves.…”
Section: Tc Mcelroy and Wj Diehlcontrasting
confidence: 54%
“…Similarly, Pecon Slattery et al (1993) reported a significant relationship between heterozygosity and age class in the hard clam Mercenaria mercenaria, but the relationship was not consistent over a 3-year sampling period. Consistency of MLH-fitness relationships has also been lacking from a series of studies on Eisenia andrei (Diehl, 1988;Audo and Diehl, 1995;McElroy et al, 1999;McElroy and Diehl, 2001), although some of this inconsistency disappears when a common set of loci are used (Audo and Diehl, 1995). In the above studies, inbreeding, migration, selective mortality, and ontogenetic effects may have affected heterozygosity-fitness relationships.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…GDFC remains difficult to investigate in the wild, and few studies have considered ecological variables in their analysis. However, there is some evidence that GDFC may be related to the harshness of the environment (Danzmann et al 1988;Dudash 1990;Borsa et al 1992;Audo and Diehl 1995;Meagher et al 1997;Crnokrak and Roof 1999;Lesbarre`res et al 2005). In this context, the alpine marmot is particularly interesting because populations occur in high alpine meadows, and must cope with a harsh climate and occasionally stressful conditions.…”
Section: Introductionmentioning
confidence: 97%
“…There is considerable evidence to suggest that genetic variation and fitness relationships may be more apparent under stressful conditions (Samollow and Soule 1983;Mitton and Grant 1984;Gentili and Beaumont 1988;Ferguson 1990;Borsa et al 1992;Audo and Diehl 1995;Pogson and Fevolden 1998;Vazquez-Dominguez et al 1998), although too much stress has also been shown to suppress such relationships . W hether the fish in this study existed under 'stressful' conditions is unknown; however, various hatchery practices are known to induce stress responses (e.g., Sharpe et al 1998 Fourth, non-genetic maternal effects could mask genetic variation-fitness relationships.…”
Section: Detection O F Genetic Vahation-fitness Relationships -Theorymentioning
confidence: 99%